Habitat Characteristics and Roaming Area of Proboscis Monkey in Bukit Semujan Swamp Forest Danau Sentarum National Park - Nyoto Santoso; Jacobus Togu Hasudungan; Sutopo; Irawan Hadiwijaya; Aripin; Yoffan Ramadhan; Syarif M Ridwan (Media Konservasi, 2023)
The proboscis monkey (Nasalis larvatus Wurmb. 1787) is an endemic and endangered primate, also very depends on its habitat characteristic. This study aims to identify habitat characteristics and roaming area of proboscis monkey. Located at Bukit Semujan within Betung Kerihun Danau Sentarum National Park, during January 2022. The methods use in this research are using scan sampling and ad libitum sampling for daily activities, roaming area of proboscis monkeys are acquired using GPS, and the vegetation type in the habitat where proboscis monkeys are active are inventoried using the checkered line method with the plot size 20 x 20 m. Research was resulted that the proboscis monkey at Bukit Semujan only found in swamp forests with daily temperatures ranging from 25,8˚C–26,9˚C and daily humidity between 97%-99%. Vegetation like Shorea blangeran is dominant and important species that occurred in swamp forest surrounding at Bukit Semujan. The species diversity in the swamp forest classified as moderate (2.76), the species evenness and the species richness index are classified as high (0.90 and 4.02). The diets of proboscis monkeys found in this study are six flora species such as kawi (Shorea blangeran), engkurun (Xanthophyllum affine), ensubal (Elaeocarpus mastersii), kenarin (Diospyros coriaceae), putat (Barringtonia acutangular), tembesu (Fragrea fragrans). One group of Proboscis monkey roaming area calculated to be 13.22 ha with daily range have an average of 579.2 meters. Sleeping trees and the edge of the swamp forest have distance 50 m with the night position shift calculated to be around 216.92 meters.